The Effect of Audit CSR, Board of Directors Meeting, and Reputation on CSR Disclosure with Audit Committee as Moderation - Ananda, Emmaculata Sac Cid (Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to examine the effect of CSR audits, frequency of board of directors meetings, and corporate reputation on the dissemination of corporate social responsibility (CSR Disclosure), with the audit committee as a moderating variable. This study was conducted on 146 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The approach used is quantitative with panel data regression using EViews 12 software. CSR analysis disclosure is measured based on the 2021 GRI Standards checklist, while the independent and moderating variables are measured through annual reports and company desire reports. The results of the study indicate that CSR audits, frequency of board of directors meetings, and corporate reputation do not have a significant effect on CSR disclosure. In addition, the audit committee does not strengthen the relationship between CSR audits and CSR disclosure. However, the audit committee is able to strengthen the relationship between the frequency of board of directors meetings and CSR disclosure, as well as between corporate reputation and CSR disclosure. These findings indicate that the effectiveness of the audit committee plays an important role in increasing the transparency and accountability of CSR disclosure when actively involved in corporate governance practices. This study contributes to the development of corporate governance and sustainability literature, especially regarding the role of audit mechanisms in encouraging CSR information disclosure in manufacturing companies in Indonesia.